Effect of fluorination pattern and extent on the properties of PCDTBT derivatives. (21st December 2015) - Cartwright, Luke; Yi, Hunan; Iraqi, Ahmed
Abstract : Fluorination ofPCDTBT derivatives at different positions and to different extents causes major changes in their properties. Abstract : Herein, we report the synthesis of a series of fluorinated dithienyl carbazole -alt -benzothiadiazoles (PCDTBT analogues) and the characterisation of their optical, electrochemical, thermal and molecular organisation in the solid state. The polymers were decorated with fluorine on either the benzothiadiazole unit, carbazole unit or both to yieldPCDTffBT, PCffDTBT andPCffDTffBT, respectively. The copolymers displayed decomposition temperatures in excess of 350 °C.PCDTffBT, PCffDTBT andPCffDTffBT displayed optical band gaps of 1.86, 1.82 and 1.88 eV, respectively. It was speculated this was a consequence of the higher molecular weight ofPCffDTBT relative to the other polymers.PCffDTBT andPCffDTffBT displayed shallower HOMO levels relative toPCDTffBT ; a consequence of fluorinating the carbazole-donor moiety. XRD studies confirmed that fluorinating the benzothiadiazole-acceptor moiety improves molecular ordering by promoting π–π stacking of polymer backbones in solid state. Interestingly, fluorinating the carbazole-donor unit does not improve π–π stacking of polymer backbones.